G95 The Drooling Reduction Intervention (DRI) trial: Is hyoscine or glycopyrronium more effective and acceptable for the treatment of drooling in children with neurodisability?. (27th April 2016) - Parr, JR; Todhunter, E; Pennington, L; Cole, M; Morrison, J; Stocken, D; Colver, A
Abstract : Aims: Drooling saliva is a common problem in children with neurodevelopmental disorders. The consequences of drooling include skin breakdown, dehydration, and damage to clothing/equipment. Hyoscine and glycopyrronium are most commonly used to reduce drooling, but there is little evidence about their relative effectiveness, or side effect profiles. We aimed to investigate in a single blind randomised controlled trial whether hyoscine or glycopyrronium is more effective and acceptable for the treatment of drooling in children with non-progressive neurodisability. Methods: Children age 3–15 years who had never received medication to treat drooling were recruited from 15 UK centres and randomised to hyoscine or glycopyrronium; stratification was by centre and drooling severity. Dose adjustment and side effect monitoring were undertaken weekly by the trial team over 4 weeks to identify the most effective dose for each child in the context of any side effects. Primary outcome data were gathered with the standardised Drooling Impact Scale (DIS) at 4 weeks by a researcher blind to treatment group status. Follow up continued to 12 weeks. Results: 90 children (median age 4.9 years) were randomised (49 hyoscine and 41 glycopyrronium). 48 children started hyoscine treatment, and 38 started glycopyrronium. By 4 weeks, 35/48 children (73%) remained on hyoscine and 33/38 (87%) on glycopyrronium; the remaining children had stopped trial medication due to side effects. By 12 weeks, 26/48 children (54%) remained on hyoscine and 31/38 (82%) on glycopyrronium. At 4 weeks there was no significant difference in DIS scores between the treatment groups suggesting both medications were equally effective at the maximum tolerated dose. However, by 4 and 12 weeks hyoscine was associated with more problematic side effects than glycopyrronium and parents were more likely to stop using hyoscine. Conclusions: Hyoscine and glycopyrronium are equally effective in treating problematic drooling in children with neurodisability. However, hyoscine is associated with more problematic side effects and is less likely to be tolerated.